The Generic Network Modeling Language (GNM) - Magtubo, Erville D. (Philippine Engineering Journal; Vol 17 No 1 (1996), 2021)
GNM is a language specifically designed to be the base language for the HERMES Project. This language provides network engineers a tool for describing and designing a network topology. With GNM, engineers can design their network in a graphical manner making it easier to be understood by other engineers. This paper discusses the basic rules in using the language.